Indicação geográfica e cafés especiais: circuito espacial produtivo e círculos de cooperação dos cafés da Região da Serra da Mantiqueira de Minas Gerais - Cogueto, Jaqueline Vigo [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
This research aims at analyzing the spatial productive circuit and the cooperation circles in the production of specialty coffee in the region bounded by the Geographical Indication of Serra da Mantiqueira do Estado de Minas Gerais region. The main purpose is to analyze material flows (grains, supplies, etc.) established between different stages of production (actual production, exchange, distribution and consumption), geographically separeted, and the relationships between the different agents, in order to analyze the organization and regulation of Gourmet Coffee and Geographical Indication production. This is about to understood if the production of higher quality and certificated origin coffees allow the development of new productive circuits, adding value and giving more autonomy and identity to the small coffee growers, when compared to traditional coffee commodity trading

A presente pesquisa tem como objetivo principal analisar o circuito espacial produtivo e os círculos de cooperação dos cafés especiais da região delimitada pela Indicação Geográfica da Serra da Mantiqueira do Estado de Minas Gerais. A proposta principal é analisar os fluxos materiais (grãos, insumos, etc.) estabelecidos entre as diferentes etapas geograficamente separadas da produção (produção propriamente dita, troca, distribuição e consumo) e as relações entre os diferentes agentes, com o intuito de analisar a organização e a regulação da produção de café Gourmet e com Indicação Geográfica. Trata-se de analisar se a produção de cafés de qualidade superior e a certificação de origem permitem o desenvolvimento de novos circuitos produtivos, agregando valor e conferindo maior identidade e autonomia aos pequenos cafeicultores, quando comparado com o tradicional comércio de café commodity
Keywords: Coffee; Café; Qualidade dos produtos; Café - Cultivo; Geografia comercial; Mantiqueira, Serra da